The Caribbean and its Linkages with the World : A GVAR Model Approach - Vargas, Mauricio (IMF Working Papers; Working Paper ;, 2019)
Using data from 1980-2017, this paper estimates a Global VAR (GVAR) model taylored for the Caribbean region which includes its major trading partners, representing altogether around 60 percent of the global economy. We provide stilyzed facts of the main interrelations between the Caribbean region and the rest of the world, and then we quantify the impact of external shocks on Caribbean countries through the application of two case studies: i) a change in the international price of oil, and ii) an increase in the U.S. GDP. We confirmed that Caribbean countries are highly exposed to external factors, and that a fall in oil prices and an increase in the U.S. GDP have a positive and large impact on most of them after controlling for financial variables, exchange rate fluctuations and overall price changes. The results from the model help to disentangle effects from various channels that interact at the same time, such as flows of tourists, trade of goods, and changes in economic conditions in the largest economies of the globe.